Laparoscopic trans teres vault suspension, a new laparoscopic method of treatment of female genital prolapse – a preliminary report - Milnerowicz-Nabzdyk, Ewa; Zimmer, Mariusz (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction : Pelvic organ prolapse (POP) is treated with a great variety of procedures and none is fully satisfactory. The aim of the study was to introduce and evaluate the effectives of laparoscopic trans teres vault suspension (LTTVS) technique as a new method for POP treatment. Material and methods: In the years 2013-2014, eight symptomatic women with grades II-IV POP underwent LTTVS procedure. The mean age of patients was 65.25 years (range from 52 to 76 years). The surgery encompassed total hysterectomy, suturing the vagina and fixation of uterosacral ligaments to the vaginal stump, fixation of stumps of round ligaments to the vaginal stump, and fixation of the vaginal stump to the anterior rectus fascia. Mean follow-up was 17.75 months (range from 6 to 27 months). Results : Eight patients were successfully operated. The symptoms of POP resolved after surgery and subjective quality of life increased. In one case a complication such as common fibular nerve injury appeared; however, it resolved after one month of physiotherapy. The other patient reported radiating pain down the leg after three months. No recurrence of vaginal stump prolapse was observed during the follow-up. Conclusions : LTTVS is a promising method for POP treatment. Due to repair with the use of native tissues, physiological placement of vaginal stump, and high efficacy it can be considered as an alternative to other POP surgeries. The method requires additional research on larger groups of patients.